Optimising teacher’s comfort in classroom: prototype design and development of vibrating insole - Alias, Ayuni Nabilah; Yaakub, Norwahida; Udin, Nurulain Mustafa (RMP Publications, 2024)
Ergonomic interventions can optimise the interaction between humans and work processes, and are particularly important for school teachers due to the increased prevalence of musculoskeletal disorders (MSDs) among them. Long working hours, prolonged sitting, awkward postures, and repetitive movements can all result in MSDs, particularly in the lower extremities. This study tasks to create a prototype, incorporating a vibrating insole, tailored to meet the comfort requirements of school teachers. The study is divided into three Phases: Phase 1 (problem identification), Phase 2 (prototype development), and Phase 3 (prototype testing). This prototype's discomfort ratings were assessed using the Borg’s scale. Initial testing was conducted to analyse the prototype's efficacy, with an emphasis on body discomfort ratings provided by teachers during one-hour teaching session. During the initial testing phase, the findings demonstrated a significant correlation between insole prototype comfort with vibrating for thigh, calf and ankle and feet discomfort rating (p<0.001) in this study. The prototype testing highlighted that school teachers' discomfort rating for ankle and feet showed significant reductions when tested with insole prototype compared to control insole (p<0.05). The prototype of insole with vibrating effect provides an alternate way to improve the ergonomic design of existing insoles while also reducing general body discomfort, notably for school teachers. However, thorough field, laboratory, and clinical testing is required to prove its efficacy in future.